Étapes : design et culture visuelle. (Paris : Pyramyd, 2012)
Created in 1994, Etapes is a well-established publication and a reference for all professionals, students and teachers working in visual communication. Etapes International delivers a critical review of the latest creations from the international designers community. With a focus on graphic design, new technology, advertising and photography it offers a wide yet pertinent panorama of the current trends in visual culture.
Keywords: Design; Fotografie; Graphic Design; Marketing